Tissue-specific and cell surface expression of human major histocompatibility complex class I heavy (HLA-B7) and light (beta 2-microglobulin) chain genes in transgenic mice. - Chamberlain, J W (1988)
We introduced the human genes HLA-B7 and B2M encoding the heavy (HLA-B7) and light [beta 2-microglobulin (beta 2m)] chains of a human major histocompatibility complex class I antigen into separate lines of transgenic mice. The tissue-specific pattern of HLA-B7 RNA expression was similar to that of endogenous class I H-2 genes, although the HLA-B7 gene was about 10-fold underexpressed in liver. Identical patterns of RNA expression were detected whether the HLA-B7 gene contained 12 or 0.66 kilobase(s) (kb) of 5' flanking sequence. The level of expression was copy number dependent and as efficient as that of H-2 genes; gamma interferon enhanced HLA-B7 RNA expression in parallel to that of H-2. In addition to the mechanism(s) responsible for gamma interferon-enhanced expression, there must be at least one other tissue-specific mechanism controlling the constitutive levels of class I RNA. Tissue-specific human beta 2m RNA expression was similar to that of mouse beta 2m, including high-level expression in liver. Cell surface HLA-B7 increased 10- to 17-fold on T cells and on a subset of thymocytes from HLA-B7/B2M doubly transgenic mice compared to HLA-B7 singly transgenic mice. The pattern of expression of HLA-B7 on thymocytes resembled that of H-2K as opposed to H-2D. These results confirm that coexpression of both human chains is required for efficient surface expression and that HLA-B7 may share a regulatory mechanism with H-2K, which distinguishes it from H-2D.